Reactive Oxygen Species: Not Omnipresent but Important in Many Locations - Herb, Marc; Gluschko, Alexander; Schramm, Michael (Frontiers in Cell and Developmental Biology, 2021)
Reactive oxygen species (ROS), such as the superoxide anion or hydrogen peroxide, have been established over decades of research as, on the one hand, important and versatile molecules involved in a plethora of homeostatic processes and, on the other hand, as inducers of damage, pathologies and diseases. Which effects ROS induce, strongly depends on the cell type and the source, amount, duration and location of ROS production. Similar to cellular pH and calcium levels, which are both strictly regulated and only altered by the cell when necessary, the redox balance of the cell is also tightly regulated, not only on the level of the whole cell but in every cellular compartment. However, a still widespread view propagated by many authors and studies is that the location of ROS production is of no major importance and that ROS randomly diffuse from their cellular source of production throughout the whole cell and hit their redox-sensitive targets when passing by. Yet, evidence is growing that cells regulate ROS production and therefore their redox balance by strictly controlling ROS source activation as well as localization, amount and duration of ROS production. Hopefully, future studies in the field of redox biology will consider these factors and analyze ROS more specifically in order to revise the outdated view of ROS as freely flowing through the cell.